Role of Domain-Specific Facets of Perceived Organizational Support During Expatriation and Implications for Performance - Takeuchi, Riki; Wang, Mo; Marinova, Sophia V.; Yao, Xin (Organization Science, 2009)
In this study, we integrated social exchange theory with a spillover perspective to examine the relationships between two facets of perceived organizational support (POS) among expatriated managers (at Time 1), their work and general adjustment (at Time 2), affective commitment (at Time 2), and job performance (at Time 3). A longitudinal survey sampled 165 expatriate managers in China across three time periods. POS in the current assignment and in off-the-job life were found to interact with each other to predict work and general adjustment. Work and general adjustment were related to higher affective commitment by the expatriate employees, which, in turn, led to better job performance. The theoretical and practical implications of these results are discussed.